Lithological And Geomorphological Structure Of Sandy Soils Of Central Fergana - V. Yu. Isakov; M.A. Yusupova; X.X. Asqarov; M.A. Marufjanov (Genius Journals, 2022)
In this article, the lithological and geomorphological structure of the sandy soils of Central Fergana was studied. Properties and characteristics of sandy soils, genesis, and chemical, agrochemical, physicochemical and ecomeliorative changes occurring in sandy soils under the influence of anthropogenic factors were studied
Keywords: Anthropogenic factor; sandy soils; mountain range depression; Ferghana Valley